Modeling method of telecommunication network resources - Yuan LIN; Yanbin WANG; Hui ZHANG; Jiahai YANG (Dianxin kexue)
Based on the well designed resource information model,the telecom operators can effectively manage the telecom network resource.A resource modeling methodology was proposed.The modeling methodology was based on the network topology and the port.The modeling process was divided into seven sub-processes:network analysis,network node identification,connection identification,equipment description,ability description,space resource analysis and model expression.In addition,a discussion on the relationships between entities had been made.Based on the modeling methodology,the LTE resource information model was constructed.Therefore,the validity of the modeling methodology was proven.Moreover,the LTE resource information model was objectively evaluated through three aspects:the complexity of the class,the ratio of depth and width of the inheritance tree and the coupling degree between classes.Results show that this model is high-quality.